Avaliação do uso da radiação ultravioleta na desinfecção de efluente de indústria de papel - Milek, Karoline Mello (2019)
Brazilian paper industry stands out in the world being among the largest producers. However, along with the great paper production is the generation of large volume of liquid effluents. One of the treatment alternatives for these effluents is the association with domestic effluent, which promotes the dilution of toxic compounds and the supply of nutrients for the treatment, but it also presents some disadvantages such as the incorporation of pathogenic microorganisms in the final effluent. Therefore, this study evaluates the ultraviolet (UV) radiation as an alternative for the disinfection of paper industry effluent in a wastewater treatment plant (WWTP) that treats combined domestic and industrial wastewater. Parameters such as liquid layer thickness, exposure time to the radiation and disinfection efficiencies were evaluated using the following indicator microorganisms of fecal contamination: Escherichia coli (E. coli) and total coliforms (TC). The thickness of liquid layers studied did not influence the disinfection efficiency and the obtained results were satisfactory from the microbiological point of view, attaining efficiency removal of 99.96 % and 100 % for TC and E. coli, respectively. As a result, it was obtained a final high-quality effluent, meeting the requirements foreseen by the current environmental laws and showing potential for reuse.